The Effect Of Supply Chain Management And Corporate Communication Skills On Production Performance At PT. Berlian Manyar Sejahtera - Nugraha, Bugi; Sianturi, Intan; Aini Rakhman, Rizqi (International Journal of Science, Technology & Management, 2023)
The aim of this research is to determine the influence of Supply Chain Management and company communication capabilities on production performance at PT. Berlian Manyar Sejahtera.This research approach uses quantitative research using an explanatory survey research design. Data collection in this research used two techniques, namely: Through questionnaires, andDocumentation methodintended to complete the data.Data analysis methods are part of the analysis process with methods appropriate to the type of research after the research data collection stage.This research uses multiple linear regression analysis. The results of the research show that 1) There is an influence of supply chain management on production performance at PT. Berlian Manyar SejahteraThus it gets highersupply chain management, the higher the production performance at PT. Berlian Manyar Sejahtera. 2)There is an influence of company communication capabilities on production performance at PT. Berlian Manyar Sejahtera.Thus, it gets higherthe company's communication capabilities, the higher the production performance at PT. Berlian Manyar Sejahtera. 3) There is an influence of supply chain management and company communication capabilities together on production performance at PT. Berlian Manyar Sejahtera. Thus, the higher the company's supply chain management and communication capabilities, the higher the production performance at PT. Berlian Manyar Sejahtera.